2022
DOI: 10.3390/cancers14153709
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Restore Cancer Cell Sensitivity towards T Lymphocytes Mediated Cytotoxicity in Pancreatic Cancer

Abstract: Despite medical advancements, the prognosis of pancreatic ductal adenocarcinoma (PDAC) has not improved significantly over the past 50 years. By utilising the large-scale genomic datasets available from the Australia Pancreatic Cancer Project (PACA-AU) and The Cancer Genomic Atlas Project (TCGA-PAAD), we studied the immunophenotype of PDAC in silico and identified that tumours with high cytotoxic T lymphocytes (CTL) killing activity were associated with favourable clinical outcomes. Using the STRING protein–pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Dacinostat (LAQ-824) has been observed to tackle cancer chemoresistance in multiple myeloma ad acute myeloid leukemia ( 99 ). One study demonstrated that dacinostat and givinostat can restore the activity of cytotoxic T lymphocytes in in pancreatic cancer cells ( 100 ). NVP-LAQ824 attenuated tumor growth and angiogenesis and enhanced VEGFR inhibitor PTK787/ZK222584-mediated inhibition of angiogenesis via upregulation of p21 and downregulation of angioprotein-2, Tie-2, VEGF, HIF-1α, and survivin ( 101 ).…”
Section: Role Of Hdac In Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Dacinostat (LAQ-824) has been observed to tackle cancer chemoresistance in multiple myeloma ad acute myeloid leukemia ( 99 ). One study demonstrated that dacinostat and givinostat can restore the activity of cytotoxic T lymphocytes in in pancreatic cancer cells ( 100 ). NVP-LAQ824 attenuated tumor growth and angiogenesis and enhanced VEGFR inhibitor PTK787/ZK222584-mediated inhibition of angiogenesis via upregulation of p21 and downregulation of angioprotein-2, Tie-2, VEGF, HIF-1α, and survivin ( 101 ).…”
Section: Role Of Hdac In Immunotherapymentioning
confidence: 99%
“…Givinostat (ITF2357) increased cell death and reduced cell proliferation in urothelial carcinoma cells and acute lymphocytic leukemia ( 113 , 114 ). Givinostat enhanced CTL sensitivity in pancreatic cancer cells ( 100 ). In addition, givinostat reduced cancer stemness and reversed transformed phenotype in glioblastoma ( 115 , 116 ).…”
Section: Role Of Hdac In Immunotherapymentioning
confidence: 99%
“…The activation of PARP1, a DNA damage-repairing enzyme, occurs because of DNA damage. PARP1 overactivity can also impair mitochondrial OXPHOS, increase ROS production, and increase ATP depletion, promoting necroptosis in PDAC [140][141][142][143][144]. Furthermore, ROS are also involved in PDAC cellular migration under the influence of the oncogenic KRAS mutation through the CCL15/ROS axis [145].…”
Section: Signaling Pathwaymentioning
confidence: 99%
“…However, pancreatic cancer eventually develops chemoresistance towards these clinically used agents. Many combination agents[ 7 , 18 , 19 ] and novel drug delivery methods[ 20 - 22 ] are currently under investigation in hope that a safe and effective treatment for pancreatic cancer patients can be found.…”
Section: Introductionmentioning
confidence: 99%